Brain and Art - Idan Segev (Frontiers Research Topics, 2014)
Could we understand, in biological terms, the unique and fantastic capabilities of the human brain to both create and enjoy art? In the past decade neuroscience has made a huge leap in developing experimental techniques as well as theoretical frameworks for studying emergent properties following the activity of large neuronal networks. These methods, including MEG, fMRI, sophisticated data analysis approaches and behavioral methods, are increasingly being used in many labs worldwide, with the goal to explore brain mechanisms corresponding to the artistic experience. The 37 articles composing this unique Frontiers Research Topic bring together experimental and theoretical research, linking state-of-the-art knowledge about the brain with the phenomena of Art. It covers a broad scope of topics, contributed by world-renowned experts in vision, audition, somato-sensation, movement, and cinema. Importantly, as we felt that a dialog among artists and scientists is essential and fruitful, we invited a few artists to contribute their insights, as well as their art. Joan Miró said that "art is the search for the alphabet of the mind." This volume reflects the state of the art search to understand neurobiological alphabet of the Arts. We hope that the wide range of articles in this volume will be highly attractive to brain researchers, artists and the community at large.